2023
DOI: 10.3390/su15043370
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Heat Integration Analysis for CO2 Removal Using Imidazolium-Based Ionic Liquid-ASPEN PLUS Modelling Study

Abstract: The recent advancement in efficient and recoverable CO2 capture solvents has been stimulated by the environmental harm resulting from the accumulation of greenhouse gases. Ionic liquids (ILs) and IL-based solvents have given rise to a novel method of CO2 collection that is highly efficient, economical, and environmentally benign. However, there is a lack of knowledge about the implementation of this process on a wider scale, and it has limitations, including high solvent costs. This simulated study shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 117 publications
0
1
0
Order By: Relevance
“…Neishabori Salehi et al also found that SAPO-34 had a CO 2 adsorption of 1.571 mmol g –1 and desorption heat of 36.74 kJ mol –1 at 298 K, and Tamnanloo et al reported a CO 2 adsorption capacity of 1.497 mmol g –1 with a high CO 2 /CH 4 selectivity at 303 K and 1.0 bar . Regarding the absorbents, the unique properties of ILs, such as low vapor pressure, volatility, high affinity, and solubility for CO 2 , , make them an efficient and environmentally suitable candidate for CO 2 capture. In particular, the ILs containing acetate-based anions have better absorption properties for CO 2 , e.g., [Bmim]­[Ac] exhibits a high affinity for CO 2 , and thus desirable CO 2 uptake at 298 K up to 2.19 mmol g –1 . According to the density functional theory prediction, the interaction energy between [Bmim]­[Ac] and CO 2 was 36.37 kJ mol –1 , indicating slow energy usage for desorption …”
Section: Introductionmentioning
confidence: 99%
“…Neishabori Salehi et al also found that SAPO-34 had a CO 2 adsorption of 1.571 mmol g –1 and desorption heat of 36.74 kJ mol –1 at 298 K, and Tamnanloo et al reported a CO 2 adsorption capacity of 1.497 mmol g –1 with a high CO 2 /CH 4 selectivity at 303 K and 1.0 bar . Regarding the absorbents, the unique properties of ILs, such as low vapor pressure, volatility, high affinity, and solubility for CO 2 , , make them an efficient and environmentally suitable candidate for CO 2 capture. In particular, the ILs containing acetate-based anions have better absorption properties for CO 2 , e.g., [Bmim]­[Ac] exhibits a high affinity for CO 2 , and thus desirable CO 2 uptake at 298 K up to 2.19 mmol g –1 . According to the density functional theory prediction, the interaction energy between [Bmim]­[Ac] and CO 2 was 36.37 kJ mol –1 , indicating slow energy usage for desorption …”
Section: Introductionmentioning
confidence: 99%